Physiotherapy care for women's health - Baranitharan, R. (Jaypee Brothers Medical Publishers, 2010)
This is the first book to deal about various women health problems, their physiotherapy management and outcome measures under one roof. Emphasis has been laid on ilustrations (flow charts) and picture wich have helped to present in an interesting and simple way